This preview shows page 1. Sign up to view the full content.
Unformatted text preview: new shortterm debt, or: New longterm debt = $324,648 – 108,800 New longterm debt = $215,848 Sales growth rate = 35% and debt/equity ratio = .75255: MOOSE TOURS INC. Pro Forma Balance Sheet Assets Current assets Cash Accounts receivable Inventory Total Fixed assets Net plant and equipment $ $ 34,155 54,945 117,315 206,415 557,550 Liabilities and Owners’ Equity Current liabilities Accounts payable Notes payable Total Longterm debt Owners’ equity Common stock and paidin surplus Retained earnings Total Total liabilities and owners’ equity $ $ $ 91,800 17,000 108,800 215,848 $ $ $ 140,000 291,395 431,395 756,043 Total assets So the excess debt raised is: $ 763,965 Excess debt = $756,043 – 763,965 Excess debt = –$7,922 44 At a 35 percent growth rate, the firm will need funds in the amount of $7,922 in addition to the external debt already raised. So, the EFN will be: EFN = $57,848 + 7,922 EFN = $65,770 26. We must need the ROE to calculate the sustainable growth rate. The ROE is: ROE = (PM)(TAT)(EM) ROE = (.059)(1 / 0.85)(1 + 0.3) ROE = .0902 or 9.02% Now, we can use the sustainable growth rate equation to find the retention ratio as: Sustainable growth rate = (ROE × b) / [1 – (ROE × b)] Sustainable growth rate = .12 = [.0902b] / [1 – .0902b] b = 1.19 This implies the payout ratio is: Payout ratio = 1 – b Payout ratio = 1 – 1.19 Payout ratio = –0.19 This is a negative dividend payout ratio of negative 19 percent, which is impossible. The growth rate is not consistent with the other constraints. The lowest possible payout rate is 0, which corresponds to retention ratio of 1, or total earnings retention. The maximum sustainable growth rate for this company is: Maximum sustainable growth rate = (ROE × b) / [1 – (ROE × b)] Maximum sustainable growth rate = [.0902(1)] / [1 – .0902(1)] Maximum sustainable growth rate = .0992 or 9.92% 27. We know that EFN is: EFN = Increase in assets – Addition to retained earnings The increase in assets is the beginning assets times the growth rate, so: Increase in assets = A × g The addition to retained earnings next year is the current net income times the retention ratio, times one plus the growth rate, so: Addition to retained earnings = (NI × b)(1 + g) 45 And rearranging the profit margin to solve for net income, we get: NI = PM(S) Substituting the last three equations into the EFN equation we started with and rearranging, we get: EFN = A(g) – PM(S)b(1 + g) EFN = A(g) – PM(S)b – [PM(S)b]g EFN = – PM(S)b + [A – PM(S)b]g 28. We start with the EFN equation we derived in Problem 27 and set it equal to zero: EFN = 0 = – PM(S)b + [A – PM(S)b]g Substituting the rearranged profit margin equation into the internal growth rate equation, we have: Internal growth rate = [PM(S)b ] / [A – PM(S)b] Since: ROA = NI / A ROA = PM(S) / A We can substitute this into the internal growth rate equation and divide both the numerator and denominator by A. This gives: Internal growth rate = {[PM(S)b] / A} / {[A – PM(S)b] / A} Internal growth rate = b(ROA) / [1 – b(ROA)] To derive the sustainable growth rate, we must realize that to maintain a constant D/E ratio with no external equity financing, EFN must equal the addition to retained earnings times the D/E ratio: EFN = (D/E)[PM(S)b(1 + g)] EFN = A(g) – PM(S)b(1 + g) Solving for g and then dividing numerator and denominator by A: Sustainable growth rate = PM(S)b(1 + D/E) / [A – PM(S)b(1 + D/E )] Sustainable growth rate = [ROA(1 + D/E )b] / [1 – ROA(1 + D/E )b] Sustainable growth rate = b(ROE) / [1 – b(ROE)] 29. In the following derivations, the subscript “E” refers to end of period numbers, and the subscript “B” refers to beginning of period numbers. TE is total equity and TA is total assets. For the sustainable growth rate: Sustainable growth rate = (ROEE × b) / (1 – ROEE × b) Sustainable growth rate = (NI/TEE × b) / (1 – NI/TEE × b) 46 We multiply this equation by: (TEE / TEE) Sustainable growth rate = (NI / TEE × b) / (1 – NI / TEE × b) × (TEE / TEE) Sustainable growth rate = (NI × b) / (TEE – NI × b) Recognize that the denominator is equal to beginning of period equity, that is: (TEE – NI × b) = TEB Substituting this into the previous equation, we get: Sustainable rate = (NI × b) / TEB Which is equivalent to: Sustainable rate = (NI / TEB) × b Since ROEB = NI / TEB The sustainable growth rate equation is: Sustainable growth rate = ROEB × b For the internal growth rate: Internal growth rate = (ROAE × b) / (1 – ROAE × b) Internal growth rate = (NI / TAE × b) / (1 – NI / TAE × b) We multiply this equation by: (TAE / TAE) Internal growth rate = (NI / TAE × b) / [(1 – NI / TAE × b) × (TAE / TAE)] Internal growth rate = (NI × b) / (TAE – NI × b) Recognize that the denominator is equal to beginning of period assets, that is: (TAE – NI × b) = TAB Substituting this into the previous equation, we get: Internal growth rate = (NI × b) / TAB Which is equ...
View
Full
Document
This note was uploaded on 07/10/2010 for the course FIN 6301 taught by Professor Eshmalwi during the Spring '10 term at University of TexasTyler.
 Spring '10
 eshmalwi
 Finance, Corporate Finance

Click to edit the document details